Identity and entrepreneurship - Oliver Falck; Stephan Heblich; Elke Lüdemann (Center for Economic Studies and ifo Institute (CESifo), 2009)
We incorporate the concept of social identity into a stylized model of occupational choice and analyze whether an individual's identity affects his or her decision to become an entrepreneur. We argue that an entrepreneurial identity results from an individual's socialization. This could be parental influence but, as argued in this paper, also peer influence. To test this empirically, we apply instrumental variable approaches to PISA data. Our findings suggest that having an entrepreneurial peer group has a positive effect on an individual's entrepreneurial intentions. Regarding entrepreneurial parents, we find a positive effect that cannot only be explained by ownership succession of the family business.
Keywords: J24; L26; Z13; 330; occupational choice; entrepreneurship; identity; peer effects; Berufswahl; Unternehmer; Soziale Beziehungen; Persönlichkeitspsychologie; Familiensoziologie; Theorie; OECD-Staaten